Knowledge of non-communicable diseases and practices related to healthy lifestyles among adolescents, in state schools of a selected educational division in Sri Lanka - A. U. Gamage; P. L. Jayawardana (BMC, 2017)
Abstract Background Behaviors established during the adolescence have life-long consequences to the onset of non-communicable diseases (NCDs) in later life. Therefore, it is essential to understand adolescents' knowledge and practices with the intention of developing preventive programs focusing on this age group. The objective of the study was to assess knowledge about selected NCDs, and lifestyle choices among school students aged 17-19 years in state schools of the Maharagama Educational Division, Sri Lanka. Methods A descriptive, cross-sectional study was conducted among students aged 17-19 years attending state schools in Maharagama Education Division. A total of 634 students were selected from 9 schools conducting Advance Level classes. Stratified sampling was done based on stream of study and the number needed from each stratum was decided according to probability proportionate to size which was followed by cluster sampling within the strata to select the classes included. Data were collected using a self-administered-questionnaire on socio-demographic characteristics and economic status; lifestyle-related practices; knowledge on Non-Communicable -Diseases. Logistic regression was used to assess the associations. Results Proportion students with good overall knowledge was 43%(n = 272). Forty-three percent (n = 275) consumed a healthy diet, and 20%(n = 129) engaged in adequate physical activity 3%(n = 18) of students were current smokers and 12%(n = 73) current alcohol users 12%(n = 73). Overall "good" knowledge about NCDs was associated with being a science stream student(OR = 3.3; 95%CI:2.1-5.2). Healthy diet was associated with female sex (OR = 2.1; 95%CI: 1.5-3.0), and adequate physical activity with male sex (OR = 2.1; 95% CI:1.4-3.2), non-science-stream (OR = 2.1; 95%CI:1.2-3.7) and upper socio economic status (OR = 2.0; 95%CI:1.3-3.0). Non-smoking was associated with overall good knowledge (OR = 4.1; 95%CI:1.2-13.7) and female sex (OR = 0;95%CI:1.5-infinity). Abstinence from alcohol was associated with being a female (OR = 6.9; 95%CI:3.4-13.9), and with mother and fathers' education level of > General-Certificate of Examinations Ordinary Level (GCE O/L) (OR = 2.9; 95%CI:1.1-8.4 and OR = 3.5; 95%CI:1.1-11.2 respectively). Conclusion Knowledge about NCDs and healthy lifestyle-practices were poor among school students aged 17-19 years. Lack of knowledge about healthy and unhealthy behaviors highlights the importance of carrying out regular surveillance for NCD risk factors, and initiating programs for the prevention of NCDs amongst adolescents.